The Contained-Rivalry Requirement and a ‘Triple Feature’ Program for Business Ethics - Martin, Dominic (2013)
This paper proposes a description of the moral obligations of economic agents. It will show that a threefold division should be adopted to distinguish moral obligations applying to their interactions in the market, obligations applying to their interactions inside business firms and obligations applying to their interactions with agents outside the market. Competition might be permissible in the first case since markets are special patterns of social interactions (called adversarial schemes). They produce their benefits when agents try to satisfy exclusive preferences at the expense of others. However, moral obligations inside the firm and moral obligations outside the market are of a different nature. This argument will be developed in the two first parts of this paper. In the third part, it will outline the relevant strengths of that account in relation with two popular views of economic agents’ moral obligations: the shareholder primacy view and the stakeholder theory.
Keywords: Stakeholder Theory; Shareholder primacy; Cooperation; Competition; Market; Rivalry; Adversarial ethics